The impact of physical activities of aerobic type in body mass and volume parameters - Myrtaj, Nazim; Shkodra, Mimoza (Journal of Education, Health and Sport, 2019)
The aim of the paper was to prove the impact of aerobically programmed physical activities on body mass and volume and reducing the ratio of fatty and non-fatty mass to 30-40-year-old females. For this purpose, the research has included a sample of 30 females who have undergone a three months program with 3 training sessions per week. Eight anthropometric variables were applied for the processing of results and the confirmation of the difference between the initial and the final state, it has been applied the t-test for dependent groups within the SPSS statistics 21.0 program. The training program with aerobic exercises applied to this group of women shows that aerobic exercises influence positively weight reduction and passive body mass and so, it should be part of fitness exercises in order to improve the health condition.